A content validity study for big data analytics implementation model - Adrian, Cecilia; Abdullah, Rusli; Jusoh, Yusmadi Yah; Atan, Rodziah (IEEE, 2019)
Despite the vast investigations that had assessed the capabilities of big data analytics (BDA), studies regarding the influential factors of BDA implementation (BDAI) are in scarcity, particularly within the organisational context. The paucity of studies on BDAI evaluation has partly motivated this study. As such, this study performed content validation in developing a BDAI model. Validation of survey instrument is essential in a quantitative research. Data were retrieved from a panel of seven big data experts, both from industries and academic. Next, the scores were analysed by incorporating item-content validity index (I-CVI) and modified kappa (K) statistics. From a set of 64 items, the content validity process discarded 9 items and retained 55 items, with the revised items proceeded for further analysis. This particular content validity study revealed that the assessed instrument can be used to develop a viable level of content validity. This study may serve as a guide amidst Information Systems (IS) researchers, especially the big data domain in devising valid and reliable instruments.